ORGANIC VS. CONVENTIONAL: A COMPARATIVE REVIEW OF HEALTH-RELATED WELFARE ISSUES AND THEIR ECONOMIC IMPACT ON POULTRY PRODUCTION - Silviu-Ionut BEIA; Dana TÄPÄLOAGÄ; Cosmin SONEA; Raluca-Aniela GHEORGHE-IRIMIA; Petronela Mihaela ROSU; Makki Khalaf Hussein AL DULAIMI; Paul-Rodian (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This review delves into the health-related welfare challenges faced by organic and conventional poultry production, highlighting the impact on bird well-being. It identifies key issues such as disease prevention, behavioural wellness, and environmental quality in both systems, with organic practices facing hurdles like antibiotic-free disease management and conventional systems dealing with antimicrobial resistance and intensive farming pressures. Additionally, the paper explores the economic aspects of these systems, analysing cost structures, market dynamics, and profitability concerns that ultimately affect both producer and consumer choices. This economic perspective is crucial as it interlinks with welfare issues to shape the overall sustainability of poultry farming. The review further advocates for an integrated approach to improve poultry welfare, emphasizing the role of technological innovations like Precision Livestock Farming, policy reforms focusing on animal welfare and sustainability, and the importance of collaboration among stakeholders including producers, policymakers, and consumers. Conclusively, addressing the welfare challenges in poultry production demands a multifaceted strategy that leverages technological advancements, supports policy changes, and fosters stakeholder engagement to enhance animal well-being, meet production goals, and satisfy consumer expectations for ethically produced poultry products.